2013
DOI: 10.1002/chem.201300864
|View full text |Cite
|
Sign up to set email alerts
|

Molecular‐Level Insights into the Oxidative Degradation of Grafted Amines

Abstract: The oxidative degradation of CO2 adsorbents consisting of amine-grafted pore-expanded mesoporous MCM-41 silica was investigated. The adsorbents were treated under flowing air at various temperatures, and the degree of deactivation was evaluated through the measurement of their CO2 adsorption capacity prior and subsequent to exposure to air. To decipher the chemical structure of surface species upon air-deactivation of grafted amines, a solvent extraction procedure was developed using a deuterated basic solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 67 publications
6
24
0
Order By: Relevance
“…The NMR spectrum of the air-deactivated BPEI was obtained in DMSO-d 6 , as well as in KOH/D 2 O following the method reported in our earlier work. 39 Interestingly, the data obtained for the extracted deactivated BPEI using both methods were consistent with each other (Fig. 5 and Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The NMR spectrum of the air-deactivated BPEI was obtained in DMSO-d 6 , as well as in KOH/D 2 O following the method reported in our earlier work. 39 Interestingly, the data obtained for the extracted deactivated BPEI using both methods were consistent with each other (Fig. 5 and Fig.…”
Section: Resultssupporting
confidence: 82%
“…Interestingly, our results further validate the solvent-extraction methodology we developed earlier for the removal of grafted species from the silica samples. 39 Indeed, although deactivated polymeric species were separated in this work by simple solvent dissolution, their structure was consistent with the grafted deactivated species removed under basic conditions. 39 Thus, the occurrence of the identified species in deactivated materials could be extrapolated to other amine-containing adsorbents.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In addition to the activation reaction of the aminosilane with water in the first step, the aminosilane can also undergo self‐polymerization in the presence of water, which is present in the toluene solvent. Sayari and co‐workers showed that the presence of water in the aminosilane solution increases aminosilane coupling on the silica surfaces, which leads to the formation of multilayers instead of a simple monolayer of grafted amines. The activated aminosilane undergoes condensation, involving the Si−OH groups of the silanol and the OH groups of the zirconia, titania, and silica nanoparticles in the fiber pores.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the degradation sequence is difficult to identify by XPS surface analysis because of technique limitations. 40 It is speculated that the NH functional groups undergo oxidative scissions and evaporative loss upon their exposure to air, although the elucidation of the degradation mechanism requires further study.…”
Section: B Aging Of Functional Groups Attached To the Surface Of Cfsmentioning
confidence: 99%